Peanut butter and jelly a play rhyme - Westcott, Nadine Bernard (E.P. Dutton, 1987)
Rhyming text and illustrations explain how to make a peanut butter jelly sandwich. Includes instructions for accompanying hand and foot motions at the end of the book.